Right To Education — A Precious Gift to Children - Mehta, Suresh Chandra (THE PRIMARY TEACHER, 2010)
The implementation of ‘Right of Children to Free and Compulsory Education Act’ (RTE) in the age group of 6–14 years from April 2010 is a welcome step and holds great significance in the history of education in India. What the Act means for children and various governments has been stated quite clearly. It has enormous implications for Universalisation of Elementary Education in the country. Now, each child whether he/ she is in school or out-of-school has the right to quality elementary education covering all aspects of his/her personality. The benefits of RTE will reach to all children only when the Act will be implemented in true spirit by all States and UTs with collaboration at all levels of implementation. To overcome challenges, effective monitoring will be needed right from the start. The present article provides a brief overview of some important features of the Act and challenges that need to be addressed by all the States and UTs of the country